Institutional Credibility in Government-Managed Tourism Storytelling: A Systematic Review - Lalu Muhammad Rifqi Nugraha; Maulina Pia Wulandari; Zulkarnain (INJECT (Interdisciplinary Journal of Communication), 2026)
This systematic literature review examines how institutional credibility, digital storytelling, and cultural identity have been conceptualized within government-managed tourism communication research. Despite growing attention to Destination Management Organization (DMO) digital communication, these constructs have been addressed in isolation: institutional credibility through crisis communication and brand trust frameworks, digital storytelling as a marketing mechanism, and cultural identity as narrative content disconnected from governance evaluation. Following PRISMA 2020 guidelines and a PICO framework, Scopus searches identified 384 records, of which 35 met the inclusion criteria. Thematic analysis produced four clusters: institutional credibility and DMO crisis communication, digital storytelling and destination branding, digital storytelling and cultural identity, and DMO digital communication practice. Cross-thematic analysis revealed a structural dissociation, as only 10 of 35 studies (28.6%) addressed all three dimensions simultaneously. Interpreted through Fombrun's Institutional Credibility (IC) framework (encompassing competence, trustworthiness, reliability, and legitimacy), findings show that existing studies engage with these dimensions selectively and without integration into a coherent governance communication account. Cultural identity emerges as an undertheorized credibility signal: when DMOs authentically integrate local heritage into storytelling, they implicitly invoke all four dimensions, yet the conditions under which audiences endorse, or contest such claims, remain untested. This review extends Fombrun's framework toward governance communication in digital tourism and proposes cultural identity authenticity as a mediating variable between storytelling and institutional credibility, reframing digital storytelling as a governance mechanism for trust-building. The most pressing gaps identified include the absence of validated IC measurement instruments and persistent Global North dominance in the literature.